A systems perspective on gaps in the person-centered sick leave and rehabilitation process: a Swedish interview study - Märit Löfgren; Karin Törnbom; Daniel Gyllenhammar; Lena Nordeman; Gun Rembeck; Cecilia Björkelund; Irene Svenningsson; Dominique Hange (Scandinavian Journal of Primary Health Care)
Background Consensus on priorities to optimize the sick leave and rehabilitation process (SRP) is lacking.Objective To explore perspectives of stakeholders in the SRP on bridging the gap between desired process scope, and actual practice, from a multi-professional, multi-organizational, and interdisciplinary approach.Design and setting Focus group interviews were conducted with various SRP frontline professionals in Region Västra Götaland, Sweden, using purposive sampling to capture a range of experiences. Participants discussed their perceptions of critical changes and priorities needed to meet patients’ SRP needs in a primary care context. All interviews were analyzed using systematic text condensation, as described by Malterud.Subjects General practitioners (n = 6), rehabilitation coordinators and licensed healthcare professionals from primary healthcare (n = 13), administrators from the Social Insurance Agency, the Employment Agency and Social Services (n = 12).Results Through data analysis, the following themes emerged: 1) The need for rules and regulations to enable coherent process governance 2) Challenges and opportunities in person-centered SRP: Professional collaboration, organizational priorities, and the need for enhanced leadership, and 3) Balancing resources and patient needs in the SRP: How to improve care quality and accessibility. In summary, participants mainly discussed how to improve process efficiency and quality of care while balancing available resources and a heavy workload. A main goal was to prevent negative spirals of suboptimal decision-making in individual cases, which could lead to increased work, unfortunate outcomes, and patient suffering.Conclusions This qualitative study indicated that gaps between a desired process scope and actual practice might be bridged by enabling coherent cross-organizational process governance, prioritizing person-centered ways of working, and balancing available resources and workload. The above changes were believed to improve process quality and overall efficiency.Trial registration The study project plan was pre-registered on September 21st, 2020, in the database FOU i VGR (researchweb.org), project number 274941.